THE The Ornaments Of Langgar Bubar, Kudus: Type And Placement - Hari Inagurasi, Libra (Jurnal Sociohumaniora Kodepena (JSK), 2023)
Fine arts have been known since prehistoric times, as seen in the caves in Maluku. During the historical period, under the Hindu-Buddhist influence, it could be seen in the temple reliefs, such as Borobudur Temple, and statues depicting Hindu gods. The decline of Majapahit, a Hindu-Buddhist kingdom on Java island, was followed by Islam's rise in the 16th century. Centers for the spread of Islam emerged on the island of Java, including Kudus. This paper aims to describe the decoration of Langgar Bubar, a sacred building that functioned as a worshipping place around the 16th century. Langgar Bubar, which means a small unfinished mosque in Javanese, is located near Menara Kudus Mosque complex. The building condition now is partially collapsed. Langgar Bubar has distinctive features: its decorative ornaments are fully carved on the brick walls. This paper discussed the type and placement of the ornaments. The method is by collecting the data from literature and survey studies, classifying data analysis, and giving the interpretation. It reveals that the ornaments do not describe living things, as it in line with the teachings of Islam. Langgar Bubar is a cultural heritage that illustrates the continuity of cultures from Hindu to Islamic period.